2016
DOI: 10.1186/s12866-016-0809-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weight and gender on intestinal bacterial community of wild largemouth bronze gudgeon (Coreius guichenoti, 1874)

Abstract: BackgroundLargemouth bronze gudgeon (Coreius guichenoti) is of economic importance in China, distributed in upstream regions of the Yangtze River in China. But it has recently dramatically declined and is close to elimination. However, there is little knowing about the character of its intestinal microbiota. This study was conducted to elucidate the intestinal microbiota of wild largemouth bronze gudgeon with different body weight and gender.ResultsThirty wild largemouth bronze gudgeon were measured for body l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 49 publications
2
43
1
Order By: Relevance
“…The physiological state can include the health status of the aquatic organisms, their feeding status, and age. Studies on the health status of aquatic organisms have commonly detected differences in sex and body weight (Li, Yan, Einar, & Wu, ) and in feeds (Akter, Sutriana, Talpur, & Hashim, ; Giannenas, Karamaligas, Margaroni, & Pappas, ; Hao, Wu, Jakovlić, & Zou, ) and feeding methods (Rungrassamee, Klanchui, Maibunkaew, & Chaiyapechara, ; Tzeng, Pao, Chen, & Weng, ; Wang, Zhang, Li, & Lin, ). The differences in the gut microbiota at different ages and the exploration of the core bacteria have been studied frequently for human and model organism intestinal microbes; however, relatively little is known regarding gut bacteria in aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological state can include the health status of the aquatic organisms, their feeding status, and age. Studies on the health status of aquatic organisms have commonly detected differences in sex and body weight (Li, Yan, Einar, & Wu, ) and in feeds (Akter, Sutriana, Talpur, & Hashim, ; Giannenas, Karamaligas, Margaroni, & Pappas, ; Hao, Wu, Jakovlić, & Zou, ) and feeding methods (Rungrassamee, Klanchui, Maibunkaew, & Chaiyapechara, ; Tzeng, Pao, Chen, & Weng, ; Wang, Zhang, Li, & Lin, ). The differences in the gut microbiota at different ages and the exploration of the core bacteria have been studied frequently for human and model organism intestinal microbes; however, relatively little is known regarding gut bacteria in aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study revealed that the intestinal microbial communities of wild largemouth bronze gudgeon ( Coreius guichenoti ) were significant different between male and female fish (Li et al . ). Stephens et al .…”
Section: The Gi Microbiota Structurementioning
confidence: 97%
“…However, LAB was not identified by 16S rRNA gene sequencing. Phenotypic males were used in this study, and this open for the speculation that differences in LAB composition may occur between gender, as some studies on aquatic animals have revealed differences in gut microbiota between male and female (Iehata, Valenzuela, & Riquelme, ; Li et al., ).…”
Section: Effects Of Soybean Products On Gut Microbiotamentioning
confidence: 99%
“…Another topic deserving attention is microbial degradation of antinutritional factors and genetically modified plants by the fish intestinal microbiota as no information is available (Ringø et al., ). When discussing microbial degradation of ANFs, it is worth to mention that the gut microbiota differs between genders in endothermic animals (Bolnick et al., ; Deusch et al., ; Mueller et al., ; Shastri, McCarville, Kalmokoff, Brooks, & Green‐Johnson, ; Zwielehner et al., ) as well as aquatic animals (Iehata et al., ; Li et al., ). Based on this fact, a controversial hypothesis can be put forward.…”
Section: Interactions Between the Immune Response And Gut Microbiota mentioning
confidence: 99%